2021
DOI: 10.1155/2021/8877779
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Urban New Technologies on the Iranian Lorry Drivers’ Behavior

Abstract: Most accidents are directly related to driving offenses, and drivers who commit more offenses are more prone to accidents. Therefore, reducing driving offenses can reduce accidents. In other words, the recognition of common driving offenses among heavy vehicle (truck) drivers and the effective factors in directing them to reduce driving offenses can consequently reduce the frequency and severity of accidents. It seems that there is a necessity for in-depth studies to carry out research on this topic. The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The more risk-taking the bank staff are, the sooner the fear of inspection will disappear and the faster the bank staff will return to the past, i.e., non-compliance with the law. The impact of human behavior on law enforcement has been confirmed in several studies [ 60 , 63 , 64 ]. To better understand the concept of risk-taking used in this study, the degree of adherence to the law over time for three samples of bank staff with different risk-taking is shown in Fig.…”
Section: Inspection and Fines Policiesmentioning
confidence: 83%
“…The more risk-taking the bank staff are, the sooner the fear of inspection will disappear and the faster the bank staff will return to the past, i.e., non-compliance with the law. The impact of human behavior on law enforcement has been confirmed in several studies [ 60 , 63 , 64 ]. To better understand the concept of risk-taking used in this study, the degree of adherence to the law over time for three samples of bank staff with different risk-taking is shown in Fig.…”
Section: Inspection and Fines Policiesmentioning
confidence: 83%
“…Globally, most RTCs are directly related to driving offences, and drivers with aggressive driving behaviour are prone to commit an offence 10. Studies indicated that dangerous driving habits such as speeding, lane deviations, tailgating, infractions, improper lane-usages, illegal turns, signal violations and right-of-way violations, result in the most RTCs in the world 11.…”
Section: Introductionmentioning
confidence: 99%